Acidophilic fungal beta-glucosidase(s) for biorefinery applications - Danielsson, Albin; Wray, Ingrid (My University, 2024)
Lignocellulose is a promising substrate for the production of chemicals and materials. In traditional biorefineries, it is first pretreated to disrupt its structure, thereby yielding acidic fractions. Therefore, enzymes from acid-tolerant organisms would be advantageous for their bioconversion. In this study, we have investigated beta-glucosidases (BGLs) from the fungi Talaromyces sp1. ASS 358-9 (Talaromyces-358), which thrives in highly acidic conditions and can utilize inhibitor-rich liquor from spruce pretreatment for growth and enzyme production. Since BGLs are crucial for biomass saccharification, we are studying the properties of differentially expressed Talaromyces-358 BGLs, aiming to find robust enzymes for biorefinery use that can withstand harsh environments like high temperatures and low pH levels. Culturing Talaromyces-358 in various liquid media revealed glucose as the most favorable substrate, significantly enhancing BGL activity over 15 days, while spruce liquor, though initially inhibitory, eventually supported significant enzyme production. The BGLs exhibited peak activity at 80°C and maintained considerable activity at 90°C, with optimal pH ranging from 4 to 6, demonstrating adaptability to harsh conditions. Enzyme activity was measured using substrates such as glucose, glucose-spruce, spruce, xylan, and xylan-spruce, with temperature measurements taken from 30°C to 90°C at pH 4, and pH measurements taken from 2 to 9 at 50°C. However, there was little to no BGL activity observed at neutral and basic pH levels.
Keywords: Beta-glucosidase (BGL); Talaromyces sp. ASS 358-9 (Talaromyces-358); Enzyme activity; Thermal stability; pH dependence; Substrate specificity; Lignocellulose bioconversion; Biorefineries